Kyasanur Forest Disease: A Narrative Review of Clinical Features, Transmission, Diagnosis and Public Health Strategies - Amartya Aaruhya; Anupama Sawal; Bhagyesh Sapkale (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Kyasanur Forest Disease (KFD) is an emerging tick-borne viral haemorrhagic illness which is endemic to the Western Ghats of southern India, caused by the Kyasanur Forest Disease Virus (KFDV), a Flavivirus transmitted primarily by haemaphysalis ticks. KFD presents after a 3-8 day incubation with abrupt fever, headache, myalgia and gastrointestinal symptoms and may progress to haemorrhagic and neurological complications. Spread of KFD to other neighbouring states underscores challenges to control the disease. Diagnosis of KFD depends upon Reverse Transcription Polymerase Chain Reaction (RT-PCR) during early viremia, which is then followed by Immunoglobulin M (IgM) Enzyme-Linked Immunosorbent Assay (ELISA), with emerging isothermal amplification techniques showing promise for field use. Measures for prevention of KFD are vaccination, carcass disposal, avoidance of ticks, along with community education. Treatment is mainly supportive, which focuses on intensive care for severe cases. Strengthening of surveillance methods, vaccinations and integrated one health strategies are essential for reducing burden of the disease.